Creative wizard on web / Wahiza A. Wahab - Wahiza, A. Wahab (2002)
Creative Wizard on Web is web site that offer printable and also send via e-mail birthday card. The main idea of this project is to let user make the card themselves, which user is given a blank worksheet and it’s up their creative and imaginative mind to create a birthday card using any images and sentiments provided. The options, either they can start creating the card from scratch or can just select any template they desired. There are few advantages that are crucial to ensure the success of this kind of web site. Most importantly, user can reduce the cost to buy ready-made card in store. The cost to buy a ready-made card is much more expensive than buying a piece of plain paper and use it to make a card themselves. Beside, by making the card themselves, the recipient will not only be surprised but will give them a priceless sentimental value. This report introduces the project and provides a description on the topics studied and researched during the literature survey. The methodology for the system development tools chosen plus, the details of system design of creative wizard web.